Profil Keterampilan Proses Sains (KPS) Siswa Kelas XI SMA Negeri 1 Ngawen pada Konsep Gelombang Bunyi - Pujiyanto, Pujiyanto; Nuroso, Harto; Sumarno, Sumarno (PGRI Kota Semarang, 2025)
Science learning should be carried out using scientific principles, including scientific attitudes, science process skills, and basic science concepts. This study aims to determine the profile of science process skills of grade XI students on the concept of Sound Waves at SMA Negeri 1 Ngawen. This study is a quantitative study with the Research and Development (R&D) method. Data were obtained by testing using the KPS assessment instrument including 6 indicators, namely observing, classifying, predicting, measuring and using numbers, concluding and communicating. The results showed that 1.47% of students were categorized as good, 19.12% were categorized as sufficient, 20.59% were categorized as less and 58.85% were in the category of very less.